Answer:
![\frac{2(c+2)}{c(c-2)}](https://tex.z-dn.net/?f=%5Cfrac%7B2%28c%2B2%29%7D%7Bc%28c-2%29%7D)
Step-by-step explanation:
![\frac{c^{2}-4 }{6c^{4}+15c^{3}}=\frac{(c-2)(c+2)}{c(6c^{3}+15c^{2}) }](https://tex.z-dn.net/?f=%5Cfrac%7Bc%5E%7B2%7D-4%20%7D%7B6c%5E%7B4%7D%2B15c%5E%7B3%7D%7D%3D%5Cfrac%7B%28c-2%29%28c%2B2%29%7D%7Bc%286c%5E%7B3%7D%2B15c%5E%7B2%7D%29%20%7D)
Identity used:
![a^{2}-b^{2}=(a-b)(a+b)](https://tex.z-dn.net/?f=a%5E%7B2%7D-b%5E%7B2%7D%3D%28a-b%29%28a%2Bb%29)
![\frac{c^{2}-4c+4}{12c^{3}+30c^{2}}=\frac{(c-2)^{2}}{2(6c^{3}+15c^{2}) }](https://tex.z-dn.net/?f=%5Cfrac%7Bc%5E%7B2%7D-4c%2B4%7D%7B12c%5E%7B3%7D%2B30c%5E%7B2%7D%7D%3D%5Cfrac%7B%28c-2%29%5E%7B2%7D%7D%7B2%286c%5E%7B3%7D%2B15c%5E%7B2%7D%29%20%7D)
Now let us divide the modified expressions:
÷ ![\frac{(c-2)^2}{2(6c^{3}+15c^{2}) }](https://tex.z-dn.net/?f=%5Cfrac%7B%28c-2%29%5E2%7D%7B2%286c%5E%7B3%7D%2B15c%5E%7B2%7D%29%20%7D)
we get:
![\frac{2(c+2)}{c(c-2)}](https://tex.z-dn.net/?f=%5Cfrac%7B2%28c%2B2%29%7D%7Bc%28c-2%29%7D)
False.
Replace x with 0 and solve:
2(0) + 3 = 0+ 3 = 3
3 is not greater than 13 so the answer is false.
Answer:
Approximately 6.4
Step-by-step explanation:
We can use the pythagorean thereom here, that tells us (a^2)+(b^2)=c^2. C is the hypotenuse, the side opposite from the right angle, while a and b are the other sides. We can insert 5 and 4 as a and b, and solve for c
:(5^2)+(4^2)=c^2
:25+16=c^2
:41=c^2
:sqrt(41)=6.4=c (We square rooted both sides. 6.4 is only rounded to the nearest hundredths place.) Hope this helps!
Answer:
1 75/100 or 3/4
Step-by-step explanation:
if you simplify 1 75/100 its 3/4
This answer to this question is 1150 km